Possible impact of the CYP2D6*10 polymorphism on the nonlinear pharmacokinetic parameter estimates of paroxetine in Japanese patients with major depressive disorders - Saruwatari, Junji (Dove Medical Press, 2014)
It has been suggested that the reduced function allele with reduced cytochrome P450 (CYP) 2D6 activity, CYP2D6*10, is associated with the interindividual differences in the plasma paroxetine concentrations, but there is no data presently available regarding the influence of the CYP2D6*10 polymorphism on the pharmacokinetic parameters, eg, Michaelis–Menten constant (K(m)) and maximum velocity (V(max)), in Asian populations. The present study investigated the effects of the CYP2D6 polymorphisms, including CYP2D6*10, on the pharmacokinetic parameters of paroxetine in Japanese patients with major depressive disorders. This retrospective study included 15 Japanese patients with major depressive disorders (four males and eleven females) who were treated with paroxetine. The CYP2D6*2, CYP2D6*4, CYP2D6*5, CYP2D6*10, CYP2D6*18, CYP2D6*39, and CYP2D6*41 polymorphisms were evaluated. A total of 56 blood samples were collected from the patients. The K(m) and V(max) values of paroxetine were estimated for each patient. The allele frequencies of CYP2D6*2, CYP2D6*4, CYP2D6*5, CYP2D6*10, CYP2D6*18, CYP2D6*39, and CYP2D6*41 were 6.7%, 0%, 10.0%, 56.7%, 0%, 26.7%, and 0%, respectively. The mean values of K(m) and V(max) were 50.5±68.4 ng/mL and 50.6±18.8 mg/day, respectively. Both the K(m) and V(max) values were significantly smaller in CYP2D6*10 allele carriers than in the noncarriers (24.2±18.3 ng/mL versus 122.5±106.3 ng/mL, P=0.008; 44.2±16.1 mg/day versus 68.3±15.0 mg/day, P=0.022, respectively). This is the first study to demonstrate that the CYP2D6*10 polymorphism could affect the nonlinear pharmacokinetic parameter estimates of paroxetine in Asian populations. The findings of this study suggest that the CYP2D6*10 polymorphism may be associated with the smaller values of both the K(m) and V(max) in Japanese patients with major depressive disorders, and these results need to be confirmed in further investigations with a larger number of patients.